Depressive symptoms among elderly inpatients of a Brazilian university hospital: prevalence and associated factors - Mendes-Chiloff, Cristiane Lora [UNESP]; Ramos-Cerqueira, Ana Teresa de Abreu [UNESP]; Lima, Maria Cristina Pereira [UNESP]; Torres, Albina Rodrigues [UNESP] (Cambridge University Press, 2008)
Background: This study aims to evaluate the prevalence of depressive symptoms and associated factors among elderly hospital inpatients.Methods: A cross-sectional study evaluated 189 participants using the Geriatric Depression Scale, the Mini-mental State Examination and the Katz and Lawton Index, to assess dependence regarding activities of daily living (ADL).Results: Most of the participants were women, aged between 60 and 92 years, with low levels of educational attainment and personal income, and non-qualified occupations. The prevalence of depressive symptoms was 56%, but only 3% had a psychiatric diagnosis registered in their medical records. Univariate analysis showed significant associations between depressive symptoms and low educational level and income, marital status, number of hospitalizations in the previous year, cognitive decline, dependence regarding basic and instrumental ADL, and death. After logistic regression, the only variables that remained significantly associated with depression were low educational level, dependence regarding basic ADL, and death.Conclusions: Depressive symptoms were independently associated with low educational level and dependence regarding basic ADL. Hospitalized elderly people with depressive symptoms were more likely to die. It is essential to diagnose and treat depression properly in this population to minimize its negative impacts.
Keywords: depressive symptoms; elderly; inpatients; prevalence; associated factors